1994
DOI: 10.1128/jvi.68.11.6836-6847.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evidence for interactions between the first, second, and fifth conserved domains of the gp120 surface glycoprotein of human immunodeficiency virus type 1

Abstract: We have used a combination of genetic and immunological techniques to explore how amino acid substitutions in the second conserved (C2) domain of gpl20 from human immunodeficiency virus type 1 (HIV-1) affect the conformation of the protein. It was reported previously (R. L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 41 publications
6
42
0
1
Order By: Relevance
“…This means that the mutations clustered in the V3 loop do not suffice but that, instead, the whole set of amino acid changes scattered over the whole gp120 molecule seems to be necessary to confer reduced sensitivity to bicyclam derivatives. This points to the importance of the three-dimensional structure of gp120 and also supports the reported interactions between several domains of gp120 (9,11,18). Apparently, the changes brought about by the detected amino acid mutations alter the conformation of gp120 in such a way that gp120 at least partially escapes the inhibitory actions of the bicyclams.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This means that the mutations clustered in the V3 loop do not suffice but that, instead, the whole set of amino acid changes scattered over the whole gp120 molecule seems to be necessary to confer reduced sensitivity to bicyclam derivatives. This points to the importance of the three-dimensional structure of gp120 and also supports the reported interactions between several domains of gp120 (9,11,18). Apparently, the changes brought about by the detected amino acid mutations alter the conformation of gp120 in such a way that gp120 at least partially escapes the inhibitory actions of the bicyclams.…”
Section: Discussionsupporting
confidence: 80%
“…This phenomenon is known for protease inhibitors (15), and reports from Willey et al (17) have indicated that a glycosylation site-deleting substitution in the C2 domain, which reduces HIV infectivity, could be functionally compensated for by a reversion substitution in the C1 domain. Moore and colleagues (11) explored the topologies of the gp120 glycoproteins of the mutant and revertant and found that the C2 substitution disrupted the CD4 binding site, which was restored to its wild-type function by the C1 compensatory substitution. Furthermore, the C2 change caused an abnormal exposure of a large segment of the C1 domain, and the segment was restored to its wild-type conformation by the reversion substitution in C1 (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in this report draw us to the conclu-sion that neutralization escape of HIV-1 from natural human sera occurs through single amino acid substitutions that affect the binding of neutralizing antibodies at multiple sites on gp120. Numerous studies have illustrated interactions between envelope regions and how changes in one region can produce alterations in noncontiguous regions (5,18,24,26,27,42,51,53). Thus, our conclusion is not unexpected.…”
Section: Discussionsupporting
confidence: 61%
“…Epitope mapping by ELISA with HxBc2 gp120 mutants. ELISA binding studies with HxBc2 gp120 mutants were performed as described previously (35,37), with the addition of the following mutants to the test panel: the mutant with a K-to-A substitution at position 59 (59K/A), 64E/A, 67N/A, 97K/…”
Section: Methodsmentioning
confidence: 99%